Pregnancy and multiple sclerosis: Risk of unplanned pregnancy and drug exposure in utero. Issue 4 (December 2019) - Smith, Andrew L; Cohen, Jeffrey A; Ontaneda, Daniel; Rensel, Mary
Background: Multiple sclerosis is a central nervous system demyelinating disease that affects women of reproductive potential. It is important to identify the frequency and risk factors of unplanned or disease-modifying therapy-exposed pregnancies to create interventions to reduce these. Methods: This retrospective, single-center, observational chart review study aims to identify risk factors for unplanned pregnancy to identify a target population for family counseling. Results: In total, 63 live births in 45 patients (20 unplanned and 43 planned) were analyzed. The percentage of unplanned pregnancy was 32%. The proportion of those receiving family planning counseling was lower in the patients with unplanned pregnancies ( p < 0.001). The main risk factors for unplanned pregnancy were younger age ( p = 0.004), disease-modifying therapy exposure ( p < 0.001), and being unmarried ( p < 0.001). Overall, 16 pregnancies had disease-modifying therapy exposure and in a subsequent study the risk for disease-modifying therapy exposure was unplanned status ( p < 0.001). Birth outcomes were not different between groups. There were more enhancing lesions in the post-partum magnetic resonance imaging of women with planned pregnancy ( p < 0.04). Conclusion: Prevention of unplanned pregnancy could lead to less disease-modifying therapy exposed pregnancies. This study suggests a targeted intervention of family planning counseling in younger, unmarried multiple sclerosis patients could potentially lead to less unintended in utero disease-modifying therapy exposure.